Multiplex fluorescent immunohistochemistry quantitatively analyses microvascular density (MVD) and the roles of TGF-β signalling in orchestrating angiogenesis in colorectal cancer - Yang, Lei; Liu, Zheng; Wen, Tao (Translational Cancer Research, 2019)
Background: Advances in multiplex fluorescent immunohistochemistry (mfIHC) techniques and digital pathology platforms allow the quantification of multiple proteins in the same tissue section and produce continuous data. Previously, we used mfIHC to establish the expressed profiles of proteins involved in TGF-β signalling in colorectal cancer (CRC). Methods: We used mfIHC to show microvascular density (MVD) by staining CD31 in the tissues from CRC patients. We further investigated the relationship between MVD and TGF-β signalling. Results: We found that the levels of MVD were significantly higher in cancer tissues than in paired normal tissues. Prognostic analysis revealed that the survival time for CRC patients with high levels of MVD was significantly shorter than that for those with low levels of MVD. Systematic analysis of the levels of MVD and TGF-β signalling proteins revealed that TGF-β signalling showed contradictory roles in sustained tumour angiogenesis. In CRC cells, the expression of VEGFA was increased by low concentrations of TGFB1 but decreased by high concentrations of TGFB1. Vessel-forming assays demonstrated that low-dose TGFB1 stimulated but high-dose TGFB1 inhibited HUVECs to form vessel tubes. Conclusions: Our analysis based on mfIHC staining in CRC tissues supports the concept that TGF-β signalling either promotes or inhibits tumour angiogenesis.